A Rare Case of Extremely Severe Heterotopic Ossification after Primary Total Hip Arthroplasty due to Persistent Mild Periprosthetic Joint Infection. (22nd May 2021) - Kinoshita, Yutaka; Nakano, Shunji; Yoshioka, Shinji; Nakamura, Masaru; Goto, Tomohiro; Hamada, Daisuke; Sairyo, Koichi
Abstract : Periprosthetic joint infection (PJI) caused by coagulase-negative staphylococci (CNS) can be a mild, persisting infection. Although heterotopic ossification (HO) is common following total hip arthroplasty (THA), the etiology of severe HO remains unclear. Herein, we describe a rare case of extremely severe HO after a PJI associated with a Staphylococcus caprae infection in a 78-year-old male patient. The patient had poorly controlled diabetes mellitus with no diabetic complications. The patient had no previous history of hip surgery, hip injury, or systemic bacterial infection. Immediately after the initial THA, he developed intermittent low-grade fever (37°C), which persisted for 3 months; consequently, he also reported mild hip pain during walking. He experienced a gradual decrease in hip range of motion within 5 years after the surgery, with progressive gait impairment. Two revision surgeries were required for the successful treatment of this difficult case. The patient's hip function improved, and the PJI was controlled following the second revision surgery. Based on the clinical course, CNS-caused PJI may lead to severe HO. This possibility warrants verification from an accumulated number of cases.